WORLD ORDER AND UNHCR'S “COMPREHENSIVE” APPROACH TO REFUGEES - Lui, Robyn (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2001)
Within the context of the changing dynamics of displacement and the increasing complexity of humanitarian issues, UNHCR distinguishes the “reactive, exile-oriented and refugee specific” activities during its early years with the “proactive, home-land oriented and holistic” activities of recent times. The task of this paper is to be explicit about the conditions under which explanations of refugee issues, particularly the concepts of international protection and durable solution are being transformed. The article also examines UNHCR’s humanitarian agenda as a response to the global refugee crisis.